Error de tipo y error de prohibición vencible e invencible bajo la perspectiva del garantismo penal - Orellana Faz, Kelly Emely (2020)
The present research project, has as its main goal to define what is the error of type and error of ban that can be invoked and invincible from the perspective of criminal guarantee, studying the dogmatic and the different doctrines that support the legal figures in question, in order to To understand with greater precision the aforementioned we proceed to expose the antecedents and the evolution throughout the history of the theory of the errors and how these have been incorporated of doctrinal form inside the regulatory norm. In Criminal Law, error equals error but not ignorance, because if so, ignorance; An individual who commits a crime believing not to do so, depending on the scenario, would be faced with an error of type or prohibition, it being unfair that he be sanctioned (if invincible) for his false knowledge or misperception, since he would lack one or more elements of the criminal offense, a trial of reproach against him being impossible in order to attribute the responsibility to the author. In Peru, for example, they have implemented their pertinent norms (penal code), the errors in mention and that in the case of Ecuador existed in the draft of the Comprehensive Organic Criminal Code, the proposal to implement them being denied, thus preventing their application In the norm, these error figures help to issue a judicial sentence under the appropriate legal guarantees, always adhering to justice towards both sides of the process........